2022
DOI: 10.1056/nejmoa2212667
|View full text |Cite
|
Sign up to set email alerts
|

Methylprednisolone for Heart Surgery in Infants — A Randomized, Controlled Trial

Abstract: Subtitle VII, Aviation Programs, describes in more detail the scope of the agency's authority.This rulemaking is promulgated under the authority described in Subtitle VII, Part A. Subpart I, Section 40103. Under that section, the FAA is charged with prescribing regulations to assign the use of airspace necessary to ensure the safety of aircraft and the efficient use of airspace. This regulation is within the scope of that authority as it amends controlled airspace at Smithfield, NC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Currently, pediatric CPB patients are routinely administered preoperative steroids to limit inflammation. However, a recent large randomized clinical trial demonstrated that prophylactic use of steroids did not improve outcomes 29 . Our data presents several therapeutic targets that have not been previously studied in the context of CPB.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, pediatric CPB patients are routinely administered preoperative steroids to limit inflammation. However, a recent large randomized clinical trial demonstrated that prophylactic use of steroids did not improve outcomes 29 . Our data presents several therapeutic targets that have not been previously studied in the context of CPB.…”
Section: Discussionmentioning
confidence: 99%
“…We performed a single-institution ancillary prospective cohort study of infants less than 1 year old enrolled in the Steroids to Reduce Systemic Inflammation after Infant Heart Surgery trial (NCT03229538), which was a multisite, randomized, double-blind, placebo-controlled trial to evaluate perioperative steroids in infants undergoing heart surgery on cardiopulmonary bypass ( 21 , 22 ). All infants enrolled at Duke between June 2019 and May 2020 could opt-in to additional urine biomarker sampling.…”
Section: Methodsmentioning
confidence: 99%
“…To identify neonates for inclusion in the PopPK analysis, we leveraged 2 prospective trials: the Steroids to Reduce Inflammation after Infant Heart Surgery (STRESS) trial (NCT03119538) 25,26 and the Opportunistic PK/Pharmacodynamic (PD) Trial in Critically Ill Children with Heart Disease (OPTIC; NCT05055830). 27 In brief, the STRESS trial is a multicenter, randomized, double-blind, placebo-controlled study evaluating the effects of methylprednisolone on outcomes after CPB.…”
Section: Patient Populationsmentioning
confidence: 99%